Plant Physiological Ecology - Lambers, Hans; Chapin III, F. Stuart; Pons, Thijs L. (Springer, 2008)
Plant ecophysiology is an experimental science that seeks to describe the physiological mechanisms underlying ecological observations. In other words, ecophysiologists, or physiological ecologists, address ecological questions about the controls over the growth, reproduction, survival, abundance, and geographical distribution of plants, as these processes are affected by interactions of plants with their physical, chemical, and biotic environment. These ecophysiological patterns and mechanisms can help us understand the functional significance of specific plant traits and their evolutionary heritage.